Age of Information: Concept, Metric and Tool for Network Control - Ephremides, Anthony; Sun, Yin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The concept of information freshness has developed over the last few years into an active and rapidly growing area of research. It has become known as the Age of Information (AoI). After its initial formal introduction, it became clear that it was very relevant (if not crucial) for numerous applications, ranging from autonomous vehicle systems, the Internet of Things, real-time computing to database access, caching, and wireless communications. More importantly, the combination of the transmission delay and sampling rate that are involved in the formulation of the AoI concept has made it clear that there are far-reaching consequences in the relationship between signal processing, information theory, and control theory at a fundamental level. In this Special Issue, we received contributions that span the full range of applications and theoretical foundations of the AoI concept, which, in fact, is also a performance metric and an analysis tool. Of special interest is the role of AoI in bridging different disciplines and the use of AoI in the analysis and optimization involved in important applications.